THE EFFECT OF TAX AMNESTY PROGRAM, REVENUE, AND E-SAMSAT ON MOTOR VEHICLE TAXPAYER COMPLIANCE IN BANDAR LAMPUNG CITY - Rudianto, Riski; Pratomo, Dimas; Suhendar, (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The purpose of this study is to identify the influence of the tax amnesty program, revenue, and e-samsat on motor vehicle taxpayer compliance in Bandar Lampung City. Between 2018 and 2023, motor vehicle tax revenue exceeded the target, although tax revenue experienced a significant decline in 2024. This study applied a quantitative method through the use of questionnaires distributed to 100 people. The sample determination applied probability sampling and simple random sampling methods through the Slovin formula and was analyzed using SPSS version 25. The research findings show that the tax amnesty program (Sig. 0.000) and e-smsat (Sig. 0.009) have a positive and significant impact on motor vehicle taxpayer compliance. Conversely, income (Sig. 0.962) does not have a significant effect. The results indicate that the tax amnesty program and e-samsat variables are effective in optimizing motor vehicle taxpayer compliance in Bandar Lampung City, while the income variable does not make a significant contribution. The research findings revealed that tax evasion (Sig. 0.000) and the E-Samsat system (Sig. 0.009) have a significant positive influence on motor vehicle taxpayer compliance, while income level (Sig. 0.962) does not have a significant influence on motor vehicle taxpayer compliance.